An Alternative Technique for Topical Application of Acidulated Phosphate Fluoride (APF) Gel: A Two-Years Double-Blind Randomization Clinical Trial (RCT) - Sorazabal, Ana Laura (2023)
Background and Objectives: Dental caries is still a dramatic public health problem. The effectiveness of an alternative technique using acidulated phosphate fluoride (APF) gel pH 3.5 was evaluated and compared with conventional treatments in reducing dental caries incidence. Materials and Methods: A double-blind randomized controlled trial was conducted, involving 180 children aged 4–11 years. Three groups were formed: NaF varnish (NaFV), APF in tray (APFt), and APF in toothbrush (APFtbru). Clinical examinations were performed using standardized criteria and the ICDAS Index was assessed. The Caries Treatment Needs Index (CTNI) was calculated. Dental examinations were conducted at baseline, 12 months, and 24 months. Results: At baseline, 16,719 dental surfaces were included, with 15,434 surfaces being sound. After 24 months, the Kaplan–Meier analysis showed significant differences between the APFtbru group and the other two groups (p = 0.03). Cox regression analysis revealed that the surfaces treated with NaF varnish had the lowest survival rates (HR = 0.51 95%CI = 0.33/0.81). Occlusal surfaces had the lowest cumulative survival, while other tooth surfaces showed similar performance. Conclusions: The alternative technique of APF gel application with a toothbrush resulted in maintaining dental health over 24 months. This technique can be cost-effective and may offer advantages over traditional fluoride varnish application.